Chloride induced corrosion of reinforcing steel evaluated by concrete resistivity measurements - Morris, Walter (2004)
The chloride threshold (ClTH) concentration for rebar corrosion initiation has received extensive attention over the last years. The chloride threshold concentration depends on several factors involving concrete composition and quality, exposure conditions and rebar surface characteristics. As a consequence, many researchers have proposed ClTH ranges that take into account the relative influence of each of these many factors. On the other hand, the electrical resistivity of concrete has proven to be an effective parameter that can be used to estimate the risk of reinforcing steel corrosion, particularly when corrosion is induced by chloride attack. The present study is based on a correlation of electrochemical parameters such as corrosion potential (Ecorr) and current density (icorr) together with concrete resistivity (ρ) and chloride concentration data. A relationship between chloride threshold values for rebar corrosion initiation and resistivity values (indicative of concrete quality) is proposed. According to this correlation, when the electrical resistivity of concrete increases from 2 to 100kΩcm, the value of ClTH increases from 0.44 to 2.32% relative to the weight of cement. © 2004 Elsevier Ltd. All rights reserved.